Removal of arsenic from drinking water - Simonič, Marjana (Sanitarno inženirstvo, 2007)
The drinking water well in Slovenska Bistrica, Slovenia, contains arsenic in concentration around 50 ?$/mu$?g/L. Therefore it is necessary to implement a technological treatment to make the water suitable for drinking. In order to do so the following technologies were suggested: activated alumina, green sand, granular ferric hydroxide and special goethite media. They were all carried out on a laboratory scale. We managed to remove arsenic below 1 ?$/mu$?g/L. Arsenic is usually found as an anion with acid characteristics in the trivalent (III) and pentavalent (V) forms. Chemical analyses of our drinking water showed that arsenic is present in pentavalent form. This means that the water is less toxic as it would be if it contained arsenic in the trivalent form. On the other hand, all the important physical chemical parameters of water remained practically unchanged after the treatment. The hygienic water quality obtained was not an issue. Finally, in addition to capability of arsenic removal, a comprehensive economic analysis of selected technologies is provided.
Keywords: pitna voda; arzen; čiščenje voda